Carbon flows from trade in harvested wood products using different accounting approaches. Issue 5 (3rd September 2021) - Guan, Zhijie; Guo, Zhiyuan; Liu, Yaofei
Abstract: Carbon flow in forest products trade will affect the report of a country's carbon stock. This will have an impact on a country's contribution of carbon flows. Based on the analysis of China's forest product trade, this paper uses the stock-change approach, the production approach and the atmospheric-flow approach to calculate the changes of China's forest products trade carbon flows. Different carbon flow measurement approaches have very different results. From the perspective of the contribution of forest products to carbon flow, the production approach of calculation for forest products trade carbon flow has the largest contribution to atmospheric carbon flows. However, the calculation results of the stock-change approach and the atmospheric-flow approach are just the opposite, that is, the calculation for forest products trade has a negative contribution to China's carbon sinks, and forest products trade has become a source of carbon emissions.